2020
DOI: 10.3389/fpsyt.2020.591407
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine Multilocus Genetic Profile, Spontaneous Activity of Left Superior Temporal Gyrus, and Early Therapeutic Effect in Major Depressive Disorder

Abstract: Objectives: This study aimed to examine the interactive effects of dopamine (DA) pathway gene and disease on spontaneous brain activity and further to explore the relationship between spontaneous brain activity and the early antidepressant therapeutic effect in patients with major depressive disorder (MDD).Methods: A total of 104 patients with MDD and 64 healthy controls (HCs) were recruited. The Hamilton Depression Scale-24 (HAMD-24) was used to measure the depression severity. Both groups were given resting-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 38 publications
1
6
0
Order By: Relevance
“…As an important part of the prefrontal cortex ( Li et al, 2013 ), the left superior frontal gyrus plays a vital role in self-awareness ( Niendam et al, 2012 ) and negative emotion regulation ( Chen et al, 2022 ), and it is involved in attention control and emotion regulation in patients with MDD ( Dutta et al, 2014 ; Hamilton et al, 2015 ). In this study, we found that patients with MDD had significantly lower ALFF in the left superior frontal gyrus than healthy controls, which is consistent with the findings of previous studies ( Liu et al, 2020 ; Zhang et al, 2021 ). The decreased spontaneous activities of brain neurons in the superior frontal gyrus may lead to low mood, anhedonia, and excessive negative self-evaluation in patients with MDD ( Guo et al, 2013 ).…”
Section: Discussionsupporting
confidence: 93%
“…As an important part of the prefrontal cortex ( Li et al, 2013 ), the left superior frontal gyrus plays a vital role in self-awareness ( Niendam et al, 2012 ) and negative emotion regulation ( Chen et al, 2022 ), and it is involved in attention control and emotion regulation in patients with MDD ( Dutta et al, 2014 ; Hamilton et al, 2015 ). In this study, we found that patients with MDD had significantly lower ALFF in the left superior frontal gyrus than healthy controls, which is consistent with the findings of previous studies ( Liu et al, 2020 ; Zhang et al, 2021 ). The decreased spontaneous activities of brain neurons in the superior frontal gyrus may lead to low mood, anhedonia, and excessive negative self-evaluation in patients with MDD ( Guo et al, 2013 ).…”
Section: Discussionsupporting
confidence: 93%
“…The STG is a component of the default mode network, which is inhibited during brain activity and excited during rest. Liu et al ( 39 ) used the rsMRI-fALFF method to study the STG in depression. They found that the lower fALFF values of STG correlated greater reductions on the Hamilton rating scale for depression, and inferred that STG neural changes were closely related to the effect of early treatment for depression.…”
Section: Discussionmentioning
confidence: 99%
“…The STG is a component of the default mode network, which is inhibited during brain activity and excited during rest. Liu et al [39] used the rsMRI-fALFF method to study the STG in depression. They found that lower the fALFF values of STG correlatedgreater reductions on the Hamilton rating scale for depression, and inferred that STG neural changes were closely related to the effect of early treatment for depression.…”
Section: Discussionmentioning
confidence: 99%